Aspek Biologi Reproduksi Ikan Tongkol Krai (Auxis thazard Laceoede, 1800) di Perairan Kedonganan, Badung Bali - Ni Luh Kade Putri Purwaningsih; Nyoman Dati Pertami; Made Ayu Pratiwi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2022)
Frigate tuna is one type of small pelagic fish that belongs to the neritic tuna (15-30 mil). This study aimed to determine the reproductive biology aspects of frigate tuna (Auxis thazard). Reproductive biology aspects can be identified by observing the sex ratio, gonad maturity level gonadal maturity index, fecundity and the size of the first gonadal maturity. Sampling was carried out in January – March 2021 with a span of 14 days at the Kedonganan Fish Landing Base. Samples were obtained from local fishermen who do one day fishing. The total fish samples observed during the study were 161 males and 174 females (335 individuals). The sex ratio of male and female tuna is 1:0.9 and is stated to be in a balanced condition. Furthermore, the gonad maturity level, during the study was dominated by levels II and III, with the gonad maturity index of male fish ranging from 6.25 to 8.31 and female fish 6.26 to 8.91. The spawning period for tuna krai in Kedonganan waters occurs in January-March and the peak of spawning occurs in March. The fecundity of krai cobs ranged from 75107 to 750470 grains (average 201.463 grains). The size of the gonads at first maturity of male krai tuna was slower than that of female tuna (321 and 336 in mm).